Characterization of Structural Geology of Faihaa Oilfield, Southern Iraq - Lazim, Aymen; Khazaal, Huda F.; Swadi, Madhi A.R. (Journal of Petroleum Research and Studies, 2022)
Faihaa Oilfield is a new exploration Iraqi Oilfield located in southern Iraq and within Mesopotamian Plain, including the Block 9 exploration area, along the Iraqi-Iranian border. The study area included Faihaa Oilfield (in Iraq) and Yadavaran Oilfield (in Iran). They belong to one anticline (Dome) structure separated by the Iraqi-Iranian border, without a geological boundary between the fields. The current study aims to achieve structural geology analysis to the study area (Faihaa/Yadavaran structure). The structural analysis included geometric and genetic analyses of the study area. According to geometric and genetic analyses results, the Faihaa/Yadavaran structure is classified as an anticline, gentle, upright, non-plunge, and asymmetrical. According to thickness variation, there are two types of formations’ folds are recognized, Thickened and Supratenuous fold generated by two folding mechanisms bending and buckle mechanisms. Bending form Supratenuous fold, perhaps due to the vertical uplift of salt structure and/or basement faults, while buckle produces Thickened fold because of the parallel tectonic movement causes collision between Arabian Plate and Eurasian Plate. Consequently, a special strain pattern was formed and the reservoir quality in the crest of Mishrif and Yamama Formations was the best. The fold axis of the Faihaa/Yadavaran structure has a Boomerang shape, whereas it is almost straight from south to the center of the structure, then tends to the NW with different deviations over the study area formations. This direction may be due to the anticlockwise rotation of the Arabian Plate motion. The results of geometric and genetic analyses revealed that may be Faihaa/Yadavaran structure is one structural trap formed by tectonic activities; Hormuz salt structures, reactivated Basement faults, and Collision between Arabian and Eurasian Plates. The intensity of the tectonic activities of the study area maybe be less than surrounding Oilfields, therefore, the Faihaa Oilfield formation’s depth was deeper than adjacent Oilfields.